Validity Of Teaching Materials Based Project Based Learning On Renewable Energy For Phase E - Nur Anisa; Darvina, Yenni; Desnita, Desnita; Gusnedi, Gusnedi (Jurnal Pendidikan Tambusai, 2023)
Changes in learning demands over time mean that the curriculum in education also changes. The new curriculum currently being used is the Merdeka curriculum. This curriculum change requires educators to be prepared to prepare learning materials that are appropriate to learning objectives. This research purpose to develop based teaching materials project-based learning on phase E renewable energy materialsvalid. This research includes research and development research carried out through 4D models. This research was only carried out in three research stages, namely the define, design and development stages. Research have limitation in development stage to determine product validity. Validity analysis was carried out on four components which include appropriateness of content, language, presentation and graphics. The data collection instrument used was a validity assessment questionnaire using a Likert scale. Validity data analysis using the V'Aikens equation. The research results showed that based teaching materials project-based learning Phase E renewable energy material is considered to have high validity. So, the teaching materials developed are suitable for use in physics learning for class X high school renewable energy material.